Effect of Lengthening the School Day on Mother's Labor Supply - Contreras, Dante; Sepúlveda, Paulina (Published by Oxford University Press on behalf of the World Bank, 2019)
This article examines how a policy oriented toward a specific group within the population can have collateral effects on the economic decisions of other groups. In 1996, the Chilean government approved the extension of the school day from half- to full-day school. This article exploits the quasi-experimental nature of the reform's implementation by time, municipality, and age targeting of the program in order to examine how the maternal labor supply is affected by the childcare subsidy implicit in the lengthening of the school day. Using data from the Chilean socioeconomic household survey and administrative data from the Ministry of Education for 1990–2011, we estimate that, on average, there is a 5 percent increase in labor participation and employment rates of single mothers with eligible children (between 8 and 13 years old) with no younger children, who are the group that would be mainly affected by the policy. No significant labor supply responses are detected among others mothers with eligible children.